THE ABSENCE OF DIDACTIC VALUES IN CHILD LITERATURE: A STUDY IN THE TWO PICTUREBOOKS - Jatmiko, Rahmawan; Alvanita, Alvanita (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2022)
In children's literature, it is important to present positive educational values in order to develop the character of children as the main target. However, not all children's literary works contain educational valuesThis paper discusses two children’s picturebooks, The Very Hungry Caterpillar by Eric Carle and I am The Dog by Daniel Pinkwater, from a reader-oriented perspective. The two picturebooks are seen as the representation of children’s literature of the modern era which tends to give more pleasure, enjoyment and entertainment than educational values. This study questions the absence of didacticism in the works, especially dealing with instructional elements, and interprets it based on its impact on children as their target readers. It uses a participatory research method which places the researchers in the center of the study object, to read, observe and interpret the data. It applies reader-response criticism proposed by Woflgang Iser, and accordingly treats the two picturebooks as literary works. The result shows instead of displaying the didacticisms, both of the books support the freedom and creativity, and satisfy children’s curiosity.